The Effect of the Implementation of Green Accounting on Company Value in the Pharmaceutical Sub-Sector Listed on the Indonesia Stock Exchange in 2019-2024 - Shabrina Salzabila; Sahmin Noholo; Siti Pratiwi Husain (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effect of implementing green accounting on company value in the pharmaceutical sub-sector listed on the Indonesia Stock Exchange during the period 2019–2024. The focus of this research is on pharmaceutical companies that are expected to integrate sustainable practices into their financial and operational reporting. A quantitative approach was employed using a simple linear regression analysis method. The data utilized in this research are secondary data obtained from annual reports and sustainability reports published by the companies through the Indonesia Stock Exchange. The sample was determined using a purposive sampling technique, resulting in 8 companies that met the criteria, with a total of 34 observations across six years. The findings of this study demonstrate that the implementation of green accounting has a positive and significant effect on company value. This result suggests that the higher the level of green accounting adoption, the greater the improvement in company value that can be achieved. The implication of these findings emphasizes the importance of adopting green accounting practices as part of corporate strategy to enhance financial performance and sustainability, especially in industries with high environmental impacts such as pharmaceuticals.